Post-germination changes in Hevea brasiliensis seeds proteome - Wong, P.F.; AbuBakar, Sazaly (2005)
Two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and mass spectrometry methods were established and utilized to examine the changes in protein expressions associated with post-germination of Hevea brasiliensis seed. No significant differences in the total number of proteins were observed but characteristic protein spots were present in both proteomes. The mature dry seed proteome contained clusters of proteins of about 36.5 and 23 kDa at pH 4-7 and a group of basic proteins at similar to pH 10. The presence of the 23 kDa proteins was markedly reduced in the post-germinated seed proteome. Approximately 60 of the proteins noted in the germinated seed proteome matched those of the mature dry seeds, with the remaining 40 protein spots as either unmatched or unique to the germinated seed proteome. Of the proteins detected, a putative beta-glucosidase, starch branching enzyme IIb and a MutT/nudix family of protein that were decreased in abundance in the germinated seed proteome and two proteins, acidic lectin and gibberellin 20-oxidase found unique to the mature dry seed proteome were identified by mass spectrometry. This report highlights the potential of using 2D-PAGE and mass spectrometry as means for identification of H. brasiliensis proteins and studying its seeds germination processes. (c) 2005 Elsevier Ireland Ltd. All rights reserved.